Markierte Intonation im wissenschaftlichen Vortrag. Eine Fallstudie - Marta Rogozińska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The purpose of this paper is to describe so-called “marked” intonation. What this means is that the intonation contour is indicated by a sharply rising pitch. This is a case study that focuses on the forms and functions of that type of rising intonation patterns which occur not in questions (interrogative mood) but in statements (indicative mood). The linguistic data consists of audio recording and transcriptions taken from the GeWiss, a comparative corpus of spoken academic language. The analysis shows that intonation contours are not subordinate to grammar and that they do not depend on modality.